Occupational risk factors for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection among healthcare personnel: A cross-sectional analysis of subjects enrolled in the COVID-19 Prevention in Emory Healthcare Personnel (COPE) study. (9th March 2022) - Howard-Anderson, Jessica R.; Adams, Carly; Sherman, Amy C.; Dube, William C.; Smith, Teresa C.; Edupuganti, Neena; Chea, Nora; Magill, Shelley S.; Espinoza, Daniel O.; Zhu, Yerun; Phadke, Varun K.; Edupuganti, Srilatha; et al.
Abstract: Among 353 healthcare personnel in a longitudinal cohort in 4 hospitals in Atlanta, Georgia (May–June 2020), 23 (6.5%) had severe acute respiratory coronavirus virus 2 (SARS-CoV-2) antibodies. Spending >50% of a typical shift at the bedside (OR, 3.4; 95% CI, 1.2–10.5) and black race (OR, 8.4; 95% CI, 2.7–27.4) were associated with SARS-CoV-2 seropositivity.